주식 듀레이션을 이용한 기대수익률 횡단면 분석 - 문성제; Sungjeh Moon; 송준혁; Joonhyuk Song (Seonmul yeongu (Online), 2019)
본 연구에서는 주식 듀레이션을 활용하여 주식 수익률의 횡단면을 분석하였다. 1991년부터 2018년까지 전체 KOSPI 주식(상장폐지 종목 포함) 대상으로 주식 듀레이션과 각각의 기대수익률을 확인한 결과 듀레이션이 짧을수록 리스크 프리미엄이 더 높은 주식 듀레이션 퍼즐(equity duration puzzle) 현상을 발견하였다. 이는 전통적인 CAPM이나 Fama and French 3요인 모형 등으로 설명되지 않는 이례적 현상이다. 또한, 주식듀레이션은 3요인 모형의 HML과는 구별되는 별도의 중요한 위험 요인으로 3요인 모형에 주식 듀레이션 요인을 추가한 4요인 모형은 기존의 벤치마크 모형 대비 우월한 가격결정 능력을 지니는 것으로 확인되었다. We analyze the cross-sectional expected return of KOSPI stocks using equity duration. From 1991 to 2018, we calculate equity durations for the KOSPI listed stocks (including de-listed stocks) and find that the shorter the equity duration, the higher the risk premium. Using the 4-factor model with equity duration added to the benchmark 3-factor model, the explanatory power of the 4-factor model is superior to that of the existing benchmark model in accounting for risk premiums. This is an unusual finding that is not readily explainable by the traditional CAPM or the Fama-French 3-factor model. This can be interpreted that the equity duration is a separate and significant risk factor dissociated from the HML of the 3-factor model.